2021
DOI: 10.17221/60/2020-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a magnetic field on the phenolic composition and virus sanitation of raspberry plants

Abstract: A magnetic pulse treatment led to an increase in the Raspberry bushy dwarf Idaeovirus-free microplants’ output and their phenolic composition change. The greatest output of the virus-free raspberries microplants (80–82%) was marked after complex treatment with pulsed and rotating magnetic fields with a time-changing frequency from 3.2 to 51 Hz, as well as with a pulsed magnetic field with a frequency from 1 to 10 Hz. The pulsed and rotating magnetic fields’ complex effect resulted in the gallic and salicylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The phenylpropanoid biosynthesis pathway also includes the production route of salicylic acid (SA), a known phytohormone participating in the plant’s response to stress. SA levels were shown to increase after the use of the pulsed magnetic field on raspberry plants ( Upadyshev et al, 2021 ). This phytohormone is known to participate in the activation of many genes involved in the plant’s response to stress, including pathogen attack.…”
Section: Resultsmentioning
confidence: 99%
“…The phenylpropanoid biosynthesis pathway also includes the production route of salicylic acid (SA), a known phytohormone participating in the plant’s response to stress. SA levels were shown to increase after the use of the pulsed magnetic field on raspberry plants ( Upadyshev et al, 2021 ). This phytohormone is known to participate in the activation of many genes involved in the plant’s response to stress, including pathogen attack.…”
Section: Resultsmentioning
confidence: 99%
“…So far, it has been shown that magnetic-pulse treatment leads to a change in the phenolic composition of raspberry microplants, increasing the CA content in tissues by 33% comparing with the control. The biochemical composition of raspberry microplants was drastically affected under magnetic-pulse treatment conditions [8]. However, scarce data exist on the effect of magnetic fields on the biosynthesis of low-molecular-weight metabolites by microplants of Pyrus communis L.…”
Section: Of 30mentioning
confidence: 99%
“…Treatment using a magnetic field affects plants enzymes and hormonal systems [25], thus affecting the growth of plant stems. Figure 3 shows the pattern of plant stem growth at the age of 7-49 days.…”
Section: Plant Stem Growth Patternmentioning
confidence: 99%